2011
DOI: 10.1007/s10562-011-0565-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface Composition and Catalytic Evolution of Au x Pd1−x (x = 0.25, 0.50 and 0.75) Nanoparticles Under CO/O2 Reaction in Torr Pressure Regime and at 200 °C

Abstract: Au x Pd 1-x (x = 0, 0.25, 0.5, 0.75, 1) nanoparticle (NP) catalysts (8-11 nm) were synthesized by a onepot reaction strategy using colloidal chemistry. XPS depth profiles with variable X-ray energies and scanning transmission electron microscopy (STEM) analyses show that the as-synthesized Au x Pd 1-x (x = 0.25 and 0.5) bimetallic NPs have gradient alloy structures with Au-rich cores and Pd-rich shells. The evolution of composition and structure in the surface region corresponding to a mean free path of 0.6-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 41 publications
9
64
0
1
Order By: Relevance
“…Accordingly, it appears neither case behaves as expected for the bulk materials. The balance of cohesive energies favours Cu segregation 38 (the higher cohesive energy element being expected to be favourably located in the core, where more bonds with like atoms are possible), but this is not dependant on which gases are 20 present. As outlined in the introduction, for many bimetallic nanoparticles it has been found that they restructure on exposure to reactive gases, such as O 2 , as a result of competition between oxide formation enthalpy and surface free energy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, it appears neither case behaves as expected for the bulk materials. The balance of cohesive energies favours Cu segregation 38 (the higher cohesive energy element being expected to be favourably located in the core, where more bonds with like atoms are possible), but this is not dependant on which gases are 20 present. As outlined in the introduction, for many bimetallic nanoparticles it has been found that they restructure on exposure to reactive gases, such as O 2 , as a result of competition between oxide formation enthalpy and surface free energy.…”
Section: Discussionmentioning
confidence: 99%
“…41 Although electronic effects have been invoked to explain this involving sub-surface nickel altering the properties of the copper, the present results offer an alternative explanation -nickel rather than copper may be segregated to the surface under the conditions of the reaction. CuNi has also recently been identified by theory and experiment to be an active and highly selective 20 catalyst for methanol synthesis from syngas. 3 Given the strong likelihood of nickel segregation in such catalysts under reducing conditions, their optimisation and development for use as practical catalysts would considerably benefit from an improved understanding of this behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations